Insolvent employer, dismissal, termination and retrenchment of employees: a study on whether employee's claims arising out of employment is adequately protected / Azman Azizan, Suraya Hanim Abdul Rahim and Azwari Kamaruddin - Azizan, Azman; Abdul Rahim, Suraya Hanim; Kamaruddin, Azwari (2009)
The maxim "easy to hire difficult to fire" is the terminology which most of the employer should practice. No employer having hired a person at considerable cost and having exposed the person to training, formal or otherwise, will want to terminate the person. However, when an employee has an attitude problem or whose work performance is not up to the expectations, his service can be terminated by the employer simply by invoking the termination clause in the employment contract. The employer has to follow certain rules and procedures and only at the end of it he could terminate the services of a non-performing employee. The dismissal (either unfair or wrongful), termination and retrenchment are the major sanctions against employees for breach of their contract of service. An employee is employed by the employer under the contract of employment. An employer who wrongfully terminates the contract is liable to an action for wrongful dismissal or unfair dismissal, if the dismissal of the employee were not done in accordance to the provisions (unfair procedure). The same applies for retrenchment, which relates to the right of the employer to reduce the number of his employees, in situations where there is an excess of the workforce or where there is an economic recession.